NEUROPROTECTIVE EFFECT OF SARGASSUM ILICIFOLIUM TURNER C. AGARDH ON ACETYLCHOLINESTERASE ACTIVITY AND ATTENUATION OF SCOPOLAMINE-INDUCED AMNESIA IN RODENTS - M, Sumithra; G, Arunachalam; G, Arunachalam; V, Chitra; G, Arunachalam; K, Gowri; V, Chitra; V, Chitra; K, Gowri; K, Gowri (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT Objective: In day to day life, occupational stress is responsible for oxidative stress by altering sleep cycle. Scopolamine induction of amnesia correlates to stress-induced amnesia in youngsters. Hence, the present study was aimed to investigate the anti-amnesic effect of ethanolic extract and ethyl acetate fraction of Sargassum ilicifolium Turner (C. Agardh) against scopolamine. Methods: In this study, seven groups of animals were used and scopolamine (0.4 mg/kg b.wt/intraperitoneally) was administered to all groups except positive control to induce memory loss. Elevated plus maze, Morris water maze served as an exteroceptive behavioral model in testing memory in young rats. Brain acetylcholinesterase, a biomarker enzyme was estimated. Finally histopathology of cerebral cortex was performed. Results: The extract and fraction treated group showed an interesting result in memory scores, and the significant enzyme inhibition might be responsible to attenuate acetylcholine in cholinergic neurons to enhance memory. Finally, histopathology of cerebral cortex proved the neuroprotective effect of S. ilicifolium. All the results were statistically significant. Conclusion: Neuroprotective role of S. ilicifolium Turner C.Agardh was highlighted well in this study and it will be interesting infuture to dissect out the kinetics of individual components in the fraction and to strengthen the phytomolecule role by insilico studies. Keywords: Learning, Memory, Acetylcholinesterase, Sargassum ilicifolium Turner (C. Agardh).